The Role of Chlamydia trachomatis Polymorphic Membrane Proteins in Inflammation and Sequelae among Women with Pelvic Inflammatory Disease - Brandie D. Taylor; Toni Darville; Chun Tan; Patrik M. Bavoil; Roberta B. Ness; Catherine L. Haggerty (Hindawi Limited, 2011)
Chlamydia trachomatis polymorphic membrane proteins (Pmps) may increase genital tract inflammation and play a role in virulence. Antibody levels for PmpA, PmpD, and PmpI, measured in densitometric units, were assessed among a pilot sample of 40 C. trachomatis-infected women with mild-to-moderate clinical PID. Women who expressed antibodies to PmpA were less likely to achieve pregnancy (40.0% versus 85.7%; 𝑃=0.042) and less likely to have a live birth (0.0% versus 80.0%; 𝑃=0.005) compared to women who did not express antibody to PmpA. Women who expressed antibodies to PmpI were more likely to have upper genital tract infection (61.5% versus 20.0%; 𝑃=0.026). However, seropositivity to PmpI and PmpD did not modify the risk of reproductive sequelae or inflammation. Seropositivity to chlamydial PmpA may represent a biomarker of increased risk of sequelae secondary to infection with C. trachomatis.